Neoplastic transformation inactivates specific trans-acting factor(s) required for the expression of the thyroglobulin gene. - Avvedimento, V E (1988)
The expression of rat thyroglobulin gene is repressed following the transformation of rat thyroid cells with Kirsten murine sarcoma virus. The expression of a reporter gene fused to the thyroglobulin promoter is down-regulated in transformed thyroid cells in transient or in stable transfection assays. DNase and exonuclease III cleavage-protection analysis reveals that a promoter binding activity located at -60 base pairs from the transcription start site is substantially reduced in transformed thyroid cells. The repression in the transformed cells of the reporter gene joined to the thyroglobulin promoter can be reversed by fusion with normal differentiated thyroid cells. Fusion of transformed thyroid cells to liver cells does not reactivate the reporter under control of the thyroglobulin promoter.